Kinetika Adsorpsi Zat Warna Tartrazina Menggunakan Limbah Ampas Tahu sebagai Adsorben - Matheis F.J.D.P. Tanasale; Yusthinus T Male; Nina B Garium (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2020)
It has been conducted a research about the utilization waste of tofu as adsorbent of tartrazine dye. Utilization waste of tofu as adsorption because tofu contains protein which has the power adsorption of amino acids that form a zwitter ion. The purpose of this study was to determine the adsorption process and adosrption kinetics model of tartrazine dye by waste of tofu as adsorbent. Making the adsorbent is done by making waste of tofu into powder with a size of 100 mesh. The method used in the analysis of tartrazine dye is using UV-Vis. Adsorption of of tartrazine dye using waste of tofu at concentrations of 50 ppm and a contact time of 80 minutes with weight adsorbent 0.3 g. The two isotherms were used that Langmuir isotherm and Freundlich isotherm, the adsorption studies of tartrazine dye adsorbent waste of tofu follow Freundlich adsorption isotherms with a correlation coefficient (R2) of 94.4%, KF is 0.0026 mg/g and n is 0.5621. Adsorption kinetics of of tartrazine dye adsorbent waste of tofu following the model of adsorption Ho pseudo-second order with a correlation coefficient (R2) of 100%, Xe is 1.7761 mg/g and k2,ads is -0.6550 g/mg minutes. The mechanism adsorption of of tartrazine dye with waste of tofu as adsorbent is chemisorpsi process.